Marilyn McCord Adams How a Theologian Works - Helmer, Christine 1965- (2018)
The article discusses the significance of the scholarship of theologian Marilyn McCord Adams, particularly her incorporation of philosophy in her teaching. It examines McCord Adams's ruminations on the connection between free will and evil, informed by her experiences as a minister to AIDS patients in Los Angeles, California, and in her theological scholarship.
Keywords: ADAMS, Marilyn McCord; Christianity; FREE will & determinism; GOOD & evil; Religious Aspects; Theologians -- United States; THEOLOGY & philosophy